An integrated methodology to define Protection Zones for groundwaterbased drinking water sources: an example from the Tuscany Region, Italy - Menichini, Matia; Da Prato, Simone; Doveri, Marco; Ellero, Alessandro; Lelli, Matteo; Masetti, Giulio; Nisi, Barbara; Raco, Brunella (Acque Sotterranee - Italian Journal of Groundwater, 2015)
Water is an essential economic and social resource. It is also finite and vulnerable. For Europe, this generally accepted understanding has been translated into the European and National Directive (2000/60/EC, D.Lgs. 152/2006). This law has led to an increased awareness of the role of the resource and its importance in the socioeconomic, cultural, and political realms. To protect this resource, safeguard zones for drinking water sources must be delineated. In Italy, a drinking water source such as a well or spring is to be protected by means of a three-level safeguard zone: an absolute safety zone close to the source, a respect zone depending on groundwater travel time, and a Protection Zone. The aim of this paper is to describe an integrated methodology used to define the Protection Zone. The work, developed within the framework of a project of the Institute of Geosciences and Earth Resources (IGG-CNR) and funded by the Tuscany Region Administration through "Consorzio Lamma", focused on the delineation of the Protection Zones for several abstraction points located throughout the regional territory. The proposed methodology for protecting drinking water sources described in this paper integrates geological, hydrogeological, and hydrogeochemical methodologies. The approach includes a definition of the hydrostratigraphy of the aquifer systems, estimates of the water volume, and the quantification of inflows and outflows, as well their interrelationships. By means of this integrated methodology, fifteen Protection Zones were defined; each of these zones was divided in two areas according to their relative importance to supplying a drinking water source. The Protection Zones were further validated by means of hydrogeological and isotopic budget calculations.